Corruption Risk Management: Power Distance, Organisational Culture and Corruption - Ach Maulidi; Bonnie Soeherman; Aisyaturrahmi; Fidelis Arastyo Andono (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Introduction/ Main Objective: The aim of this study is to examine the complex relationship between power distance, organisational culture, and corruption. Background Problems: The study of corruption, organisational culture, and power distance has been addressed by numerous scholars, yet these investigations often fail to account for the complexity and interplay of these factors within distinct organisational environments. Research Methods: We distributed questionnaires to public servants in Indonesian local governments and analysed the collected data using PLS-SEM. Findings: While earlier research has tended to isolate individual variables or oversimplify complex dynamics, our study demonstrates the complex interactions between power distance, organisational culture, and corruption. Interestingly, familial, gender, and marital factors show negligible direct effects on corruption, challenging assumptions that personal demographics may have predictive power over such systemic behaviors. However, the influence of organisational culture on corruption, demonstrated by a significant negative effect, presents a compelling finding. Conclusion: We provide new insights that have both theoretical and practical implications. Our findings call for a shift in how corruption is understood and addressed, moving away from simplistic models and towards a more holistic approach that considers the broader organisational and systemic factors at play.